Módulo de seguridad informática aplicando la autentificación de doble factor para la Empresa Home Office S. A.S. - Barriga Rivera, Byron Alfredo (2021)
In the current era, technologies have evolved to the point of being present in our daily lives, so improving the security of all computer systems has become a priority for companies. The company Home Office S.A.S, dedicated to the purchase and sale of digital products requires a high security in all its computer processes, being exclusive access to authorized personnel its highest priority regarding computer security For this reason, a computer security module was implemented applying two-factor authentication for the company Home Office S.A.S., with the purpose of managing and validating user information, detecting and neutralizing computer attacks and ensuring exclusive access for its authorized users. In the development of this research several methods and methodologies were used depending on each of its phases, being for the development of the computer module the cascading methodology and the analysis of the factors of possession through bibliographic sources. The evaluation of the computer module was carried out through the Delphi method under the security metrics of the ISO 25010 standard, to perform this process two cycles were used, the first without the implementation of double-factor authentication and the second with the implementation. Resulting in the first interaction a compliance of 83% in general and in the second compliance with 100% of all the metrics, improving the computer security of the Home Office S.A.S company.